2017
DOI: 10.1007/978-3-319-57186-7_21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Energy Hotspots: A Case Study of the Very Fast Decision Tree

Abstract: Large-scale data centers account for a significant share of the energy consumption in many countries. Machine learning technology requires intensive workloads and thus drives requirements for lots of power and cooling capacity in data centers. It is time to explore green machine learning. The aim of this paper is to profile a machine learning algorithm with respect to its energy consumption and to determine the causes behind this consumption. The first scalable machine learning algorithm able to handle large v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…Despite this massive scale of efforts towards developing energyefficient solutions to deep learning problems, there are surprisingly very few studies that measure energy for deep learning workloads [4, 22,28,45,52]. We consolidate our observations from these works and attribute the lack of adoption of energy-use as an evaluation criteria to the following reasons:…”
Section: Introductionsupporting
confidence: 54%
“…Despite this massive scale of efforts towards developing energyefficient solutions to deep learning problems, there are surprisingly very few studies that measure energy for deep learning workloads [4, 22,28,45,52]. We consolidate our observations from these works and attribute the lack of adoption of energy-use as an evaluation criteria to the following reasons:…”
Section: Introductionsupporting
confidence: 54%
“…In another publication, the authors [3] already confirmed the high energy impact of the functions involved in calculating the best attributes. This matches with our energy model, and motivates the reasons and objectives for nmin adaptation:…”
Section: Nmin Adaptationmentioning
confidence: 91%
“…concept drift adaptation, the parameters of such algorithms are fixed from the beginning of the execution. We have observed that having fixed parameters leads to the algorithm making unnecessary computations, thus increasing its energy consumption [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ou ainda, trabalhos que usam algoritmos de AM para predizer o desempenho e o consumo de energia sobre a execução de uma aplicação científica [Siegmund et al 2015, Wu et al 2016, Ferreira et al 2017, Klôh et al 2019. Porém, ainda existem poucos trabalhos que avaliam o consumo de energia dos algoritmos de AM [Li et al 2016, Garcia-Martin et al 2017, Yang et al 2017, Abdelhafez et al 2019, García-Martín et al 2019.…”
Section: Trabalhos Relacionadosunclassified
“…Em [Garcia-Martin et al 2017] são avaliados os hotspots de energia do algoritmo Very Fast Decision Tree (VFDT). A implementação, o treinamento e teste do algoritmo são realizados no framework Massive Online Analysis (MOA) [Bifet et al 2010] e a energiaé medida com a ferramenta Jalen [Noureddine et al 2015].…”
Section: Trabalhos Relacionadosunclassified